Supervised physical activity and the incidence of gestational diabetes mellitus: a systematic review and meta-analysis. (31st December 2023) - Bennett, G.; King, N.; Redfern, K.; Breese, B. C.
Abstract: Background: Gestational diabetes mellitus (GDM) characterized by dysfunction in maintaining glucose homeostasis is recognized as the most common metabolic complication associated with pregnancy leading to adverse clinical outcomes for maternal and fetal health. Although previous analysis of the findings from randomized controlled trials (RCTs) support that regular physical activity reduces the incidence of GDM during pregnancy, less is known about the optimal timing of intervention with respect to trimester stage. Objectives: To examine the interaction between both the timing and volume of supervised physical activity interventions on reducing the incidence of GDM during pregnancy. Study design: Electronic databases including CINAHL, Embase, Medline and the Cochrane library were searched for records up to 29 September 2022. Eligibility criteria were RCTs including standard antenatal care + supervised physical activity intervention without dietary modification vs. those receiving standard antenatal care alone in women with no previous diagnosis of GDM, type 1 or type 2 diabetes mellitus. Results: Of the 3411 records identified, 20 RCTs comprising 6732 participants were included. It was found that supervised physical activity interventions decreased GDM risk when started within the first trimester (RR: 0.57, 95% CI: 0.41–0.79; p  = .001) and by accumulating >600 MET·min·wk −1 of exercise (RR: 0.77, 95% CI: 0.60–0.98; p  = .03) compared with standard antenatal care alone. Women with a BMI ≤25 kg/m 2 experienced the greatest risk reduction in GDM following supervised exercise training (RR: 0.51, 95% CI: 0.34–0.75; p  = .001). Conclusion: Supervised physical activity reduces the incidence of GDM during pregnancy. It is recommended that pregnant individuals achieve a minimum of 600 MET·min·wk −1 of physical activity during the first trimester in order to reduce their odds of developing GDM. Attaining a healthy pre-pregnancy BMI is also an important determinant for the prevention of GDM with exercise.